Antigen presentation plays positive roles in the regenerative response to cardiac injury in zebrafish - João Cardeira-da-Silva; Qianchen Wang; Pooja Sagvekar; Janita Mintcheva; Stephan Latting; Stefan Günther; Radhan Ramadass; Michail Yekelchyk; Jens Preussner; Mario Looso; Jan Philipp Junker; Didier Y. R. Stainier (Nature Communications, 2024)
Abstract In contrast to adult mammals, adult zebrafish can fully regenerate injured cardiac tissue, and this regeneration process requires an adequate and tightly controlled immune response. However, which components of the immune response are required during regeneration is unclear. Here, we report positive roles for the antigen presentation-adaptive immunity axis during zebrafish cardiac regeneration. We find that following the initial innate immune response, activated endocardial cells (EdCs), as well as immune cells, start expressing antigen presentation genes. We also observe that T helper cells, a.k.a. Cd4+ T cells, lie in close physical proximity to these antigen-presenting EdCs. We targeted Major Histocompatibility Complex (MHC) class II antigen presentation by generating cd74a; cd74b mutants, which display a defective immune response. In these mutants, Cd4+ T cells and activated EdCs fail to efficiently populate the injured tissue and EdC proliferation is significantly decreased. cd74a; cd74b mutants exhibit additional defects in cardiac regeneration including reduced cardiomyocyte dedifferentiation and proliferation. Notably, Cd74 also becomes activated in neonatal mouse EdCs following cardiac injury. Altogether, these findings point to positive roles for antigen presentation during cardiac regeneration, potentially involving interactions between activated EdCs, classical antigen-presenting cells, and Cd4+ T cells.